Varieties of Unionism. Strategies for Union Revitalization in a Globalizing Economy - Croucher, Richard (Relations industrielles / Industrial Relations, 2006)
The article reviews the book, "Varieties of Unionism, Strategies for Union revitalization in a Globalizing Economy," edited by Carola M. Frege and John Kelly.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Globalization; International; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unionization